Parental Separation and Well-Being of Youths - Rainer Winkelmann (Institute for the Study of Labor (IZA), 2003)
This paper uses recent data for Germany and a new outcome variable to assess the consequences of parental separation on the well-being of youths. In particular, it is considered how subjective well-being, elicited from an ordinal 11-point general life satisfaction question, differs between youths living in intact and non-intact families, holding many other potential determinants of well-being constant using ordered probit regressions. The main finding of this study is that living in a non-intact family has not the hypothesised large negative effect on child well-being.
Keywords: C25; I31; J12; 330; child welfare; educational attainment; happiness; German Socio-Economic Panel; Ehe; Jugendliche; Lebensstandard; Lebensqualität; Schätzung; Deutschland; Lebenszufriedenheit